Application of Deep Learning Using Convolutional Neural Network (CNN) Method For Women’s Skin Classification - anton, Anton; Nissa, Novia Farhan; Janiati, Angelia; Cahya, Nilam; Astuti, Puji (Scientific Journal of Informatics, 2021)
Facial skin is skin that protects the inside of the face such as the eyes, nose, mouth, and others. Facial skin consists of several types, including normal skin, oily skin, dry skin, and combination skin. This is a problem for women because it is difficult to recognize and distinguish their skin types this is what causes some women to find it difficult to determine the right make-up and care products for their skin types. In this study, the Convolutional Neural Network (CNN) method is the right method for classifying women's skin types from the age of 20-30 years by following several stages using Python 3.5 programming with a depth of three layers and the results of this research using the CNN method get the results of the accuracy value good at 67%